Radiological protection. Minimum criteria for electron paramagnetic resonance (EPR) spectroscopy for retrospective dosimetry of ionizing radiation. Ex vivo human tooth enamel dosimetry Part 2, (28th July 2020) - British Standards Institution,
No abstract available